Réponses

2012-10-30T19:26:31+01:00

A=25x^2-9+(5x-3)(7x+5)=25x^2-9+35x^2+25x-21x-15=60x^2+4x-24

B=(2x-3)(4x+2)+(-2x+3)(7x-6)=8x^2+4x-12x-6+(-14x^2+12x+21x-18)=-x^2+25x-24

C=(4x-6)(3x+7)+(2x-3)(8x+3)=12x^2+28x-18x-42+16x^2+6x-24x-9=28x^2-8x-51

D=2x(4x+5)+16x^2+40x+25=8x^2+10x+16x^2+40x+25=24x^2+50x+25

E=9-48x+64x^2-(6+2x)(3-8x)=9-48x+64x^2-(18-48x+6x-24x^2)=88x^2+6x-9

F=100x^2-25+(20x+10)(2x-4)=100x^2-25+40x^2-80x+20x-40=140x^2-60x-65

G=(7x+8)^2-(3x-4)^2=49x^2+112x+64-(9x^2-24x+16)=40x^2136x+48

H=100-(2x+1)^2=100-(4x^2+4x+1)=-4x^2-4x+99

I=121x^2-(2x-5)^2=121x^2-(4x^2-20x+25)=117x^2+20x-25

J=25x^2-9+(5x-3)^2-(5x+6)(5x-3)=25x^2-9+25x^2-30x+9-(25x^2-15x+30x-18)=

25x^2+45x-18

bonne chance

2012-10-30T19:28:58+01:00

A= 60x²+19x-33

B= -6x²+25x-24

C= 28x²-8x-51

D= 24x²+50x+25

E= 80x²-6x-9

F= 140x²-60x-65

G= 40x²+136x+48

H= -4x²-4x+99

J= 117x²+20x-25

K= 25x²-45x+18

Voilà les résultats, si tu veux que je te détail certains calculs, hésite pas ;)!